Waldenström Macroglobulinemia Diagnosed by Ultrasonography‐Guided Biopsy of the Right Perinephric Tumor - Shingo Morinaga; Shigeyuki Aoki; Motoi Tobiume; Genya Nishikawa; Fusako Higuchi; Yuusuke Ikenohata; Manabu Honda; Hiroe Kubo; Tomoko Sawada; Yoshiaki Yamada (IJU Case Reports)
ABSTRACT Introduction Waldenström macroglobulinemia is a low‐grade B‐cell lymphoma characterized by lymphoplasmacytic lymphoma infiltration of the bone marrow and immunoglobulin M (IgM) protein. Case Presentation An 80s‐year‐old male presented to our hospital with chief complaints of weight loss and general fatigue. Computed tomography (CT) showed homogeneous tumor around the kidney with elevated soluble Interleukin‐2 receptor, serum IgM, and β2‐microglobulin levels. Histopathological analysis by ultrasonography‐guided biopsy revealed dense lymphocytic proliferation, plasmacytoid differentiation, and Dutcher bodies, positive for CD20, CD138, and IgM, but negative for CD3 and CD5, consistent with lymphoplasmacytic lymphoma. Bone marrow biopsy revealed infiltration of the lymphoplasmacytic lymphoma. The patient received four courses of bortezomib, cyclophosphamide, and dexamethasone along with dexamethasone, rituximab, and cyclophosphamide therapy. Twelve months after treatment, CT revealed only slightly enlarged abdominal para‐aortic lymph nodes. Conclusion Malignant lymphoma in perinephric lesions is a relatively rare condition; however, a definitive diagnosis can be obtained by ultrasound‐guided biopsy, allowing early initiation.